Economic analysis of beef cattle and groundwater - Ha, Sang Su (Kansas State University, 2022)
As climate change progresses, extreme weather events such as floods, droughts, and abnormal high and low temperatures frequently appear. These extreme changes in weather conditions result in modifying existing production strategies throughout agriculture. Kansas' two most important agricultural sectors, beef cattle and crop production, are in need of adjusting their production strategies reflecting on climate change. This study quantifies how changing climate affects the beef carcass performance and whether adverse impacts on carcass quality can be addressed with index-based insurance. Additionally, we analyzed the possibility of an economic approach to allocating groundwater pumping rights in Western Kansas without infringement of legal ownership. Groundwater is essential for grain production in Western Kansas but has slowly been depleted. The structure of water use rights in Kansas has not been substantially altered for many years. The first chapter examines the influence of weather stress and water quality on beef carcass yield index and marbling score. These attributes, in part, determine the market value of beef. The estimation results indicate that prolonged exposure to cold and heat stress led to deteriorated yield index and a lower marbling score. The yield index increased with longer exposures to heat or cold stress. Furthermore, the heat stress impact is larger than that of cold stress on meat productivity, and the marbling score was more vulnerable to the effect of cold stress. In order to determine how weather stresses affect profitability, we carried out a simulation analysis of beef value reduction. Simulation analysis results indicated that weather stress steadily increased producers' losses, although impaired marbling scores attributed to heat stress had a relatively limited effect on profitability. Estimation results indicate that 40 hours of exposure to heat stress corresponds to approximately a $30 loss per head. Alternatively, 40 hours of cold stress is predicted to cause a loss of about $15 per head. Accessibility to water is essential for beef production, but the impact of water quality on beef carcass outcomes has not been researched in depth. The potential of hydrogen (pH) in groundwater slightly affected beef performance. We also confirmed no significant relationship between transportation and marbling scores was observed. Additionally, we calculated fair premium rates for a weather-index livestock insurance product that mitigates the potential and partial losses from extreme weather. The second chapter analyzed a new groundwater permit allocation scheme for Kansas and the potential resulting groundwater savings and effects on crop production. The primary purpose of Chapter 2 was to quantify the marginal value of groundwater and assess the possibility of market-based permit trading to reduce groundwater extraction without negatively impacting the well-being of producers. The High Plains Aquifer (HPA) spreads out across eight states from South Dakota to Texas and provides more than 90% of irrigation water used in that region. Ninety-seven percent of groundwater extraction from HPA has been used for irrigation, and 76.5% of farms rely on groundwater in Kansas (USDA-NRCS 2013). Despite improvements in groundwater management in Kansas, the major problem of groundwater depletion continues. As awareness of the limitations of centralized governance approaches based on pumping restrictions has increased, localized and decentralized market-based approaches have gained popularity. Data were collected through the use of the Water Information Management and Analysis System (WIMAS) in Kansas. We used local crop-water production functions based on Crop Water Allocator (CWA) developed by the Kansas State University Research and Extension (KSRE). We calculated the marginal value of each irrigation well using crop-water functions. These values are used to set the permit transaction price. Kansas groundwater is worth an average of $782.73 per acre-foot. The area with the highest value is Groundwater Management District (GMD) 4 at $902; the area with the lowest groundwater value is GMD3 at $727. Our simulations found increased farm household income in all regions with permit trading. A Uniform Double Auction generates an average income of $10,772 for groundwater sellers, and buyers may earn $13,046 after groundwater sellers have received their payment. From a regional perspective, the GMD3 region had the highest average buyer income of $15,267 and the highest average seller income of $13,840. In Discriminatory Double Auction, Sellers earned an average of $13,529 from groundwater permit sales, while buyers earned an average additional income of $10,499. However, the ultimate goal of actual groundwater use reduction through water trading is not easily accomplished due to many (65%) unused authorized quantities in Kansas. The benefit from permit trading must outweigh the economic motivation for groundwater saving. The market-based approach could promote sustainable groundwater use under the current Kansas groundwater use trend, providing more returns to farmers with higher yields. Based on these calculated values, the market-based approach increased the private net benefit, as sellers and buyers of permits are better off after trading. To make permit trading successful in Kansas with groundwater use saving, one must overcome barriers such as issuing new water permits each year, high non-use rates, and non-infringement on those who received water rights before 1964. The Kansas State Government and farmers should begin discussions and administrative support to pursue a sustainable agricultural economy due to the conservation for future generations and groundwater resources.
Keywords: Comprehensive climate index; Beef carcass performance; Weather index insurance; Weather stress; High Plains Aquifer; Groundwater permit trading